Periodic trends and hidden dynamics of magnetic properties in three series of triazacyclononane lanthanide complexes. Issue 23 (22nd May 2019) - Suturina, Elizaveta A.; Mason, Kevin; Botta, Mauro; Carniato, Fabio; Kuprov, Ilya; Chilton, Nicholas F.; McInnes, Eric J. L.; Vonci, Michele; Parker, David
Abstract : In three structurally related series of nine-coordinate lanthanide(iii ) complexes, solution NMR studies and DFT/CASSCF calculations have provided key information on the magnetic susceptibility anisotropy. Abstract : In three structurally related series of nine-coordinate lanthanide(iii ) complexes (Ln = Tb, Dy, Ho, Er, Tm and Yb) based on triazacyclononane, solution NMR studies and DFT/CASSCF calculations have provided key information on the magnetic susceptibility anisotropy. Both experimental and computational approaches have revealed a poor correlation to Bleaney's theory of magnetic anisotropy. CASSCF calculations suggested that the magnetic susceptibility is very sensitive to small geometric variations within the first coordination sphere, whereas DFT analyses indicate that it is the thermal accessibility of low energy vibrational modes that may lead to distortion. Parallel NMRD and EPR studies on the three Gd(iii ) complexes revealed good correspondence in estimating the electronic relaxation time. The Gd(iii ) tris-pyridinecarboxylate complex possesses a very long electronic relaxation time making it a promising starting point for responsive gadolinium EPR probe design.